PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI - Sutianingsih Sutianingsih; Rikco Yulianto (JURNAL ILMIAH EDUNOMIKA, 2021)
Purpose of this study is to empirically analyze the influence of leadership, organizational culture, job promotion on job satisfaction and employee performance. The population in this study is the employees of the Regional Water Company of Sragen Regency with a total of 90 employees. This study took a sample of 90 respondents with the sample method used by the researcher was the census, namely the entire population was sampled. The analytical technique used is to use an instrument test which includes validity and reliability tests, linearity tests, regression analysis, path analysis, t test, F test, coefficient of determination test and correlation analysis. The results of the leadership hypothesis test have a significant positive effect on employee job satisfaction. Organizational culture has a significant positive effect on employee job satisfaction. promotion has no significant negative effect on employee job satisfaction. Leadership has a significant positive effect on employee performance. Organizational culture has a significant positive effect on employee performance. Promotion has no significant negative effect on employee performance. Job satisfaction has a significant positive effect on employee performance. The results of the F test can be concluded that the variables of leadership, organizational culture, job promotion and job satisfaction have a significant positive effect on employee performance at the Regional Water Company of Sragen Regency. The total R2 value of 0.944 means that the performance of employees in the Regional Water Company of Sragen Regency is explained by the variables of leadership, organizational culture, job promotion and job satisfaction of 94.4% and the remaining 5.6% is explained by other variables outside the research model as an example of competence, work stress and work environment. Based on the results of the analysis, both direct and indirect effects, the indirect influence of leadership on performance through job satisfaction is the most effective or dominant influence on performance when compared to other paths. Job satisfaction variable proved to be effective or in research proved to be a mediating variable. Keywords: Leadership, Organizational Culture, Promotion, Satisfaction, Performance